Retinal Glaucoma Detection Using Deep Learning Algorithm - Maurya, Tanya; Kala, Lalitha; Manasa, Kaveti; Gunasekaran, Kanimozhi; C, Umayal (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Glaucomatic retinopathy is a degenerative eye disease that is assessed as it progresses, making it necessary to examine it more frequently. The lack of professional observers has led to computer-aided monitoring. A novel method of analyzing retinal images by detecting vessels and exudates has been proposed to analyze retinal vascular disorders. A curvelet-based method improves the retinal image to allow for better vessel detection. The discrete curvelet transform (DCT) is applied, and its coefficients are applied to obtain the image ridges using multi-structure elements. With connected component analysis (CCA) and length filtering, false edges are removed. In this work, noise removal is modified by a suitable nonlinear function. The modified function parameters are derived by using fast DCT (FDCT) coefficients, which enhance weak edges while eliminating noise. Mathematical morphogen plane process using Discrete Wavelet Transform, Curvelet Transform, Orthogonal Transform, and Fuzzy Segmentation on a minimum of 10 features such as Mean, Variance, Entropy with the data set trained images on 15 images using NN (neural network) training is implemented and NN classifier based Normal or Abnormal is applied. Simulation using MATLAB Simulink is done and comparisons among Discrete Wavelet, Curvelet, Orthogonal transform, and fuzzy segmentation are executed and the blood vessels segmentation resulted in promising results.